2022
DOI: 10.1111/1751-7915.14062
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme cascade converting cyclohexanol into ε‐caprolactone coupled with NADPH recycling using surface displayed alcohol dehydrogenase and cyclohexanone monooxygenase on E. coli

Abstract: Summary The application of enzymes as biocatalysts in industrial processes has great potential due to their outstanding stereo‐, regio‐ and chemoselectivity. Using autodisplay, enzymes can be immobilized on the cell surface of Gram‐negative bacteria such as Escherichia coli. In the present study, the surface display of an alcohol dehydrogenase (ADH) and a cyclohexanone monooxygenase (CHMO) on E. coli was investigated. Displaying these enzymes on the surface of E. coli resulted in whole‐cell biocatalysts access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Combining alcohol dehydrogenase displaying cells with cyclohexanone monooxygenase displaying cells facilitated a cascade reaction of cyclohexanol to cyclohexanone and sequentially to ε -caprolactone in a two-cell approach. 37 We also reported that two functional enzymes were successfully combined by co-display in a single-cell approach. Here, truncated variants of human cytochrome P450 1A2 (CYP1A2) and human cytochrome P450 reductase (CPR) were co-displayed on E. coli .…”
Section: Resultsmentioning
confidence: 96%
“…Combining alcohol dehydrogenase displaying cells with cyclohexanone monooxygenase displaying cells facilitated a cascade reaction of cyclohexanol to cyclohexanone and sequentially to ε -caprolactone in a two-cell approach. 37 We also reported that two functional enzymes were successfully combined by co-display in a single-cell approach. Here, truncated variants of human cytochrome P450 1A2 (CYP1A2) and human cytochrome P450 reductase (CPR) were co-displayed on E. coli .…”
Section: Resultsmentioning
confidence: 96%
“…To elucidate the affinity range of the assay, the amount of surface-displayed C-Linker-CNBD protein was determined by densitometry as described before by Tian et al, 2022 [ 50 ]. It was calculated to be 5.1 × 10 4 molecules per cell, which was in the same order of magnitude as reported before for other surface-displayed proteins [ 40 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…To elucidate the affinity range of the assay, the amount of surface-displayed C-Linker-CNBD protein was determined by densitometry as described before by Tian et al, 2022 [ 50 ]. It was calculated to be 5.1 × 10 4 molecules per cell, which was in the same order of magnitude as reported before for other surface-displayed proteins [ 40 , 50 , 51 ]. Since a minimum number of 10 5 cells is required for a flow cytometry sample [ 48 ], a minimum number of approximately 10 9 –10 10 receptors can be calculated per sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1.12 mM ε-caprolactone was produced using ADH and CHMO displaying whole cell biocatalysts in a ratio of 1:5 after 4 h in a cell suspension of OD 578nm 10. Furthermore, the reaction cascade as applied provided a self-sufficient regeneration of NADPH for CHMO by the ADH whole cell biocatalyst [ 159 ].…”
Section: Poster Presentationsmentioning
confidence: 99%